Effective practice and instruction: A skill acquisition framework for excellence - Willams, A. M.; Hodges, N. J. (Journal of Sports Sciences, 2023)
We revisit an agenda that was outlined in a previous paper in this journal focusing on the importance of skill acquisition research in enhancing practice and instruction in sport. In this current narrative review, we reflect on progress made since our original attempt to highlight several potential myths that appeared to exist in coaching, implying the existence of a theory-practice divide. Most notably, we present five action points that would impact positively on coaches and practitioners working to improve skill learning across sports, as well as suggesting directions for research. We discuss the importance of practice quality in enhancing learning and relate this concept to notions of optimising challenge. We discuss how best to assess learning, the right balance between repetition and practice that is specific to competition, the relationship between practice conditions, instructions, and individual differences, and why a more "hands-off" approach to instruction may have advantages over more "hands-on" methods. These action points are considered as a broad framework for advancing skill acquisition for excellence (SAFE) in applied practice. We conclude by arguing the need for increased collaboration between researchers, coaches, and other sport practitioners.